Pengaruh Kebijakan Perpajakan, Praktik Akuntansi Pajak dan GCG Terhadap Kinerja Keuangan Perusahaan Manufaktur: Sektor Kimia - Sinyari, Ni Wayan; Jaya Kusuma, Putu Sri Arta (Jurnal Akuntansi dan Pajak, 2024)
The issues in this study are about Good Corporate Governance which can have a significant influence on tax avoidance. The purpose of this study is to analyse the effect of tax policy, tax accounting practices and good corporate governance on financial performance using a quantitative approach and involving 90 populations which are financial reports for the last three years, namely from 2021-2023. Data collection instruments were taken through the Indonesia Stock Exchange online, this study uses secondary and multiple linear techniques. The results arising from the study show that there is no effect on these two variables